Prirastoslovne značilnosti robinije (Robinia pseudoacacia L.) v Sloveniji - Kadunc, Aleš (Gozdarski vestnik, 2016)
The black locust stands at 30 locations in Slovenia were analyzed. We estimated that site productivity amounts, on average, to 11.9 m3ha-1year-1. The current height and diameter increment culminate in the first decade. Growth in flysch is slightly worse. The occurrence of rot on the stump is frequent. The timber of the highest quality classes is almost not found. The mean value increment of trees decreases with diameter at breast height.
Keywords: produkcijska sposobnost rastišč; gozdna rastišča; sortimentni sestav; vrednost lesa; robinija; Robinia pseudoacacia L.